2019
DOI: 10.3390/molecules24224183
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound-Assisted Extraction Conditions Followed by Solid Phase Extraction Fractionation from Orthosiphon stamineus Benth (Lamiace) Leaves for Antiproliferative Effect on Prostate Cancer Cells

Abstract: Primarily, optimization of ultrasonic-assisted extraction (UAE) conditions of Orthospihon stamineus was evaluated and verified using a central composite design (CCD) based on three factors including extraction time (minutes), ultrasound amplitude (A), and solvent concentration (%). The response surface methodology (RSM) was performed to develop an extraction method with maximum yield and high rosmarinic acid content. The optimal UAE conditions were as follows: extraction time 21 min, ultrasound amplitudes 62 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…A similar trend was found in several previous studies reported by Syakfanaya et al [39]. A study conducted by Suhaimi et al [40] reported that UAE of more than 20 min caused a decrease of phenolic compound yields.…”
Section: Extraction Timesupporting
confidence: 90%
See 2 more Smart Citations
“…A similar trend was found in several previous studies reported by Syakfanaya et al [39]. A study conducted by Suhaimi et al [40] reported that UAE of more than 20 min caused a decrease of phenolic compound yields.…”
Section: Extraction Timesupporting
confidence: 90%
“…A study conducted by Suhaimi et al . [ 40 ] reported that UAE of more than 20 min caused a decrease of phenolic compound yields.
Figure 3.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At investigation of single-factors in uence on emodin yield, the overall trend is similar: With the increase of variables, it rst increases to a certain vertex and then decreases. For in uence of ultrasonic time, on ultrasonic extraction of rosmarinic acid from Orthosiphon stamineus Benth leaves, the similar tendency was found [47]. In general, the ultrasonic wave needs time to crush the cell walls of R. o cinale and extract the cell contents.…”
Section: Discussionsupporting
confidence: 60%
“…It means that the sinensetin is major flavonoid in studied extract genotypes. On the other hand, it was reported that sinensetin content will decrease when extraction was performed using polar solvent such as ethanol 70% 34 . This result indicated that the genotype A15 and A11 could be developed through a breeding program to get the high flavonoid and sinensetin contents of O. aristatus varieties.…”
Section: Discussionmentioning
confidence: 99%